Determination of technological capabilities reduce energy consumption and temperature for machining - Гершіков, Ілля Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
This paper defines the conditions to reduce the temperature in the machining, consisting in reducing the energy intensity of processing due to reduction in intensity of friction in the cutting zone